De-escalation of Care Through Pediatric Intensive Care Unit Liberation Rounds and a Daily Checklist. Issue 2 (March 2018) - Kawai, Yu; Rohlik, Gina M.; Neu, Lori L.; Mujic, Anna J.; Duncan, Julie M.; Feigal, Scott A.; Rowekamp, Debra J.; Fetterly, Britt M.; Fryer, Karen R.; Conlon, Patricia M.; Huskins, W. Charles; Schiltz, Brenda M.; et al.
Abstract : Introduction: Pediatric intensive care unit (PICU) Liberation Bundle1 was implemented to standardize weaning of ICU support after clinical stabilization and to prevent iatrogenicity by timely assessment of pain, extubation readiness, sedation, delirium, withdrawal, early mobilization, and family engagement. By implementing a PICU Liberation bedside rounding process and a de-escalation daily rounding checklist, we hypothesized that the PICU Liberation Bundle compliance will improve and the risk for iatrogenic conditions can be minimized. Methods: The "old" rounding process used a nursing script organized by organ systems while the "new" process (Fig. 1 ) focused on PICU Liberation Bundle elements and the addition of a physician-completed checklist (Fig. 2 ). Independent observers collected data during rounds. All checklists completed over the first 50 days after deployment were analyzed. Results: There was an increase in frequency of PICU Liberation Bundle elements discussed during the "new" process with similar rounding time compared with the "old" process (Table 1 ). The overall compliance with the checklist was 90.4% (322 of 356 total patient-days). The medical plan was modified 62 times in 14.0% (45 of 322) of the checklists completed. The 5 most frequently modified tasks were converting intravenous to per os meds (13), initiating bowel regimen (11), initiating GI prophylaxis (9), consulting physical therapy/occupational therapy/physical medicine and rehabilitation services (9), and initiating sleep enhancement protocol (6) accounting for 77.4% (48/62) of all amendments made. Conclusions: PICU Liberation rounding process improved adherence with the PICU Liberation Bundle elements, and the checklist caught numerous missed opportunities, thereby increasing the frequency of timely de-escalation of care and minimizing the risk of iatrogenic conditions without lengthening rounding time.